ROBOTICS AND AUTOMATED SURGICAL SYSTEMS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Robotics and automated systems in surgery have revolutionized modern medicine in recent years. This article analyzes the fundamental principles of robotic surgery, types of systems, and their advantages in surgical practice. The use of robotics enhances surgical precision, patient safety, and accelerates recovery. Additionally, current trends in automated systems and their future potential in medicine are discussed.
Keywords: Robotics, surgery, automated systems, minimally invasive procedures, medical technology, patient safety.